Anionic Dopant Delocalization through p‐Band Modulation to Endow Metal Oxides with Enhanced Visible‐Light Photoactivity. Issue 46 (22nd October 2019) - Song, Xianyin; He, Dong; Li, Wenqing; Ke, Zunjian; Liu, Jiangchao; Tang, Chongyang; Cheng, Li; Jiang, Changzhong; Wang, Ziyu; Xiao, Xiangheng
Abstract: An N‐doped TiO2 model reveals a conceptually different mechanism for activating the N dopant based on delocalized orbital hybridization through O vacancy incorporation. Synchrotron‐based X‐ray absorption spectroscopy, time‐resolved fluorescence, and DFT studies revealed that O vacancy incorporation can effectively stimulate the delocalization of N impurity states through p‐band orbital modulation, which leads to a significant enhancement in photocarrier lifetime. Consequently, this effect also results in a remarkable increase in the incident photon‐to‐electron conversion efficiency in the range of 400–550 nm compared to that of conventional N‐incorporated TiO2 (15 % versus 1 % at 450 nm). This work reveals the fundamental necessity of orbital modulation in the band engineering of metal oxides for driving solar water splitting and beyond. Abstract : A typical N‐doped TiO2 model reveals an anion activation mechanism based on the fundamental delocalized orbital hybridization modulation through O‐vacancy incorporation. The usefulness of the model was demonstrated for pre‐evaluating the role of dopants according to systematically experimental and theoretical studies.